Safety and Efficacy of Tirofiban for Acute Ischemic Stroke Patients With Large Artery Atherosclerosis Stroke Etiology Undergoing Endovascular Therapy - Huo, Xiaochuan; Raynald; Wang, Anxin; Mo, Dapeng; Gao, Feng; Ma, Ning; Wang, Yilong; Wang, Yongjun; Miao, Zhongrong (Frontiers in Neurology, 2021)
Objective: To investigate the safety and efficacy of tirofiban in acute ischemic stroke (AIS) patients with large artery atherosclerosis (LAA) stroke etiology, receiving endovascular therapy (EVT). Methods: Patients were divided into a tirofiban group and a non-tirofiban group. The safety and efficacy outcomes at 90-days follow-up included symptomatic intracranial hemorrhage (sICH), recanalization rate, functional outcome, and mortality. Results: Among the 649 AIS patients with LAA, those in the tirofiban group (n = 244) showed higher systolic blood pressure (BP) and NIHSS score on admission, puncture-to-recanalization time, lower frequency of intravenous thrombolysis and intra-arterial thrombolysis, higher frequency of antiplatelet, heparinization, mechanical stent retrieval, aspiration, ballon angioplasty and more retrieval times compared with those in the non-tirofiban group (n = 405) (all P < 0.05). Tirofiban was found to be associated with superior clinical outcomes in anterior circulation stroke and major stroke patients [adjusted odds ratio (OR) = 2.163, 95% confidence interval (CI) = 1.130-4.140, P = 0.02 and adjusted OR = 2.361, 95% CI = 1.326-4.202, P = 0.004, respectively] and a lower risk of mortality at 90-days follow-up (adjusted OR = 0.159, 95% CI = 0.042-0.599, P = 0.007 and adjusted OR = 0.252, 95% CI = 0.103-0.621, P = 0.003, respectively). There was no significant difference in sICH between the two groups. Conclusions: Tirofiban in AIS patients with LAA undergoing EVT is safe and may benefit the functional outcomes in anterior circulation and major stroke patients and had a trend to lower the risk of mortality.